Assembly of Free‐Standing Polypeptide Films via the Synergistic Combination of Hyperbranched Macroinitiators, the Grafting‐From Approach, and Cross‐Chain Termination. (31st May 2013) - Wibowo, Steven Harris; Wong, Edgar H. H.; Sulistio, Adrian; Guntari, Stefanie N.; Blencowe, Anton; Caruso, Frank; Qiao, Greg G.
<x xml:space="preserve">Abstract</x> Cross‐linked polypeptide‐based films are fabricated via a novel and robust method employing surface‐initiated ring opening polymerization of α‐amino acid N‐carboxyanhydrides (NCA‐ROP). The judicious combination of amine‐based hyperbranched macroinitiators and benzyl ester‐protected NCA derivatives promotes network formation by cross‐chain terminations, which allows the formation of stable cross‐linked peptide‐based capsules in a one‐pot system. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>